2014
DOI: 10.7586/jkbns.2014.16.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Pain, Muscle Strength and Flexibility according to Pinch Lift and Rubbing Manual Therapy and Stretching Application for Low Back Pain

Abstract: Purpose: This research was implemented for men in their thirties who have lower back pain to observe general activity disorder patterns during pinch lift and rubbing manual therapy (PMT) and stretching application. Methods: Participants were divided into three groups: The PMT Group used applied pinch lift and rubbing manual therapy; the STR Group used applied stretching; and the CON Group was the control group. Participants for each group received treatments that were conducted three times a week for a total f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…To effectively treat low back pain, reducing pain and increasing strength and flexibility are important ( Rainville et al, 2004 ). The application of stretching to the lumbar and leg muscles is known to alleviate low back pain and help restoration ( Paek et al, 2014 ). Among them, the stretching of the tensor fascia lata has been reported to improve the range of motion of the hip joint and pelvis and relieve low back pain ( Kippers and Parker, 1987 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To effectively treat low back pain, reducing pain and increasing strength and flexibility are important ( Rainville et al, 2004 ). The application of stretching to the lumbar and leg muscles is known to alleviate low back pain and help restoration ( Paek et al, 2014 ). Among them, the stretching of the tensor fascia lata has been reported to improve the range of motion of the hip joint and pelvis and relieve low back pain ( Kippers and Parker, 1987 ).…”
Section: Discussionmentioning
confidence: 99%
“… Sahrmann (2002) reported that most low back pain would be relieved if the trunk muscles were controlled and the flexibility of the lower extremities was increased. Paek et al (2014) reported that stretching and pinch lift and rubbing manual therapies applied to patient with lower back pain were effective for muscle strengthening, pain relief, and flexibility. The result of this study also showed that the application of stretching using a load on the tensor fascia lata connected from the pelvis to the lower extremity increased flexibility.…”
Section: Discussionmentioning
confidence: 99%